1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Substitution/Elimination to find General Solution | System of ODE's

  1. Dec 9, 2012 #1
    1. The problem statement, all variables and given/known data

    Use substitution/elimination to find the general solution.

    dx/dt = 3x-y+2t^2

    dy/dt = 4x-2y-8t^2

    2. Relevant equations

    I'm practically clueless on how to solve this problem using substitution/elimination, I'm pretty sure the way I'm doing it is completely wrong. If anyone can show me the correct approach or can show an example it would be a tremendous help.

    3. The attempt at a solution

    dx/dt = 3x - y +2t^2

    dx = (3x -y +2t^2)dt

    x = 3xt - yt + 2/3t^3

    x(1-3t) = - yt + 2/3t^3

    x = (-yt + 2/3t^3)/(1-3t)

    I know this is not the correct way but I can't find anything online, so if someone does know what to do please reply.

    Last edited: Dec 9, 2012
  2. jcsd
  3. Dec 9, 2012 #2


    User Avatar
    Homework Helper

    x is a function of t. If you integrate it, you get [itex]\int x(t)\,\mathrm{d}t[/itex], not xt. Similarly for y.

    We want to eliminate either x or y and its derivatives to get a second order ODE for whichever variable we're left with.

    Here it seems easiest to eliminate y, since the first equation tells us that
    [tex]y = 3x - \frac{\mathrm{d}x}{\mathrm{d}t} + 2t^2[/tex]
    Differentiating this gives
    [tex]\frac{\mathrm{d}y}{\mathrm{d}t} = 3\frac{\mathrm{d}x}{\mathrm{d}t}
    - \frac{\mathrm{d}^2x}{\mathrm{d}t^2} + 4t[/tex]
    You can now substitute these expressions for y and dy/dt into the second equation.
  4. Dec 9, 2012 #3
    Thanks for the response and help. Alright so here is what I did:

    y = 3x- x' + 2t^2;

    (3x- x' + 2t^2)' = 4x -2(3x- x' + 2t^2) + 2t^2;

    3x' - x'' + 2t^2' = 4x -6x + 2x' -4t^2 + 2t^2

    x'' - x' -2x = 2t^2' - 2t^2

    r^2 - r - 2 = 0

    r = 2, r = -1

    I don't know how to proceed from this point on.
  5. Dec 10, 2012 #4


    User Avatar
    Homework Helper

    The second equation is [itex]y' = 4x - 2y - 8t^2[/itex], so you should have
    (3x- x' + 2t^2)' = 4x -2(3x- x' + 2t^2) - 8t^2
    which yields
    3x' - x'' + 4t = 4x - 6x + 2x' - 4t^2 - 8t^2
    (because [itex](2t^2)' = 2(2t) = 4t[/itex]) so that
    x'' - x' - 2x = 4t + 12t^2

    You need to find a solution of
    x'' - x' - 2x = 4t + 12t^2
    and add to it the general solution of
    x'' - x' - 2x = 0
    The second part you should know. For the first part, the form of the right hand side suggests taking [itex]f(t) = at^2 + bt + c[/itex] with constants a, b and c, which you should choose so that [itex]f'' - f' - 2f = 4t + 12t^2[/itex].

    That gives you [itex]x(t)[/itex], and you can then find [itex]y(t)[/itex] from [itex]y = 3x- x' + 2t^2[/itex].
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook